Hubungan Deviasi Septum Nasi dengan Derajat Obstruksi Nasi Berdasarkan Skor NOSE - Panjaitan, Vania Christy M; Imanto, Mukhlis (Medula, 2024)
Nasal septum deviation is the occurrence of the nasal septum shifting from the midline. According to the American Academy of Otolaryngology-Head and Neck Surgery, nasal septum deviation is a common condition that affects approximately 80% of the population. The prevalence of nasal septum deviation can increase with age, reaching 72% at the age of 3-14 years old. Although the prevalence is pretty high, specific prevalence for Indonesia is still limited. Nasal septum deviation can be caused by trauma, birth mold theory and hereditary factors. Lateral  trauma of the nose can cause changes in the position of the cartilaginous septum, while frontal trauma can cause indentations, fractures and duplication of the nasal septum. Some nasal septum deviation can also be caused by compression effects on the nose during the intrauterine period and birth, as well as the use of forceps. The classification of nasal septum deviation generally uses the Mladina classification which consists of 7 types. The main symptom of nasal septum deviation is nasal obstruction, which can be measured through subjective and objective measurements. Septoplasty therapy is often performed to reduce subjective complaints. Epidemiological studies indicated that approximately 260,000 septoplasties were performed in the United States and 10,000–95,000 in Europe. The use of questionnaires such as the NOSE score helps in the degree of nasal obstruction and its effect on the patient's quality of life. Studies showed a relationship between nasal septum deviation and complaints of nasal obstruction, especially in the nasal valve area. As a diagnostic tool, CT scan and measuring the angle of septal deviation are used to determine the degree of septal deviation. In Indonesia, more research is still needed to understand the prevalence and characteristics of nasal septum deviation in more detail. Subjective and objective parameters, along with valid questionnaires such as the NOSE score, provide a holistic understanding of the impact of septal deviation on patients and help in the assessment and management of this condition.